Longitudinal changes in domains of physical activity during the transition from elementary school to high school in the U.S. - Taverno Ross, S. E.; Saunders, R. P.; Dowda, M.; Pate, R. R. (Journal of Science and Medicine in Sport, 2023)
Objectives: To describe patterns of age-related change in self-reported physical activity domains within a heterogeneous sample of boys and girls in the U.S. transitioning from elementary to high school. Design: mProspective cohort study. Methods: Participants included n=644 children recruited in 5th grade (10.5±0.5years old, 45% female) who completed the Physical Activity Choices survey at least twice over 5 time points (5th, 6th, 7th, 9th and 11th grade). Participants' self-reported physical activities were categorized into organized and non-organized activities, and a comprehensive variable was created as the product of the total number of physical activities reported in the past 5 days, the number of days spent in each activity, and the total time spent in each activity. Descriptive statistics and growth curve models (controlling for covariates) for the total sample and by sex were examined for total, organized, and non-organized physical activities from ages 10 to 17. Results There was a significant age by gender interaction (p<0.05) for time spent in non-organized physical activities. Specifically, both sexes had similar patterns of decline before age 13, while boys increased after age 13 and girls declined and then maintained. In contrast, boys and girls declined in organized physical activities from ages 10 to 17 (p<0.001). Conclusions We observed stark differences in the age-related change between organized and non-organized physical activities and marked differences in the patterns of non-organized physical activities between boys and girls. Future research should examine physical activity interventions that consider age-, sex-, and domain-specific physical activity options for youth.